Cost-effectiveness of antibiotic prophylaxis in elective cesarean section - Markus H. Jansson; Yang Cao; Kerstin Nilsson; Per-Göran Larsson; Lars Hagberg (Cost Effectiveness and Resource Allocation, 2018)
Abstract Background The proportion of pregnant women delivered by cesarean section has increased steadily during the past three decades. The risk of infection is 10-fold augmented after elective cesarean section compared to vaginal delivery. Antibiotic prophylaxis may reduce endometritis by 62% and superficial wound infection by 38% after elective cesarean section. International guidelines recommend antibiotic prophylaxis in elective cesarean section, but this procedure is not routinely followed in Sweden. Studies of costs of antibiotic prophylaxis in cesarean section show conflicting results and are based on substantially different incidence of postoperative infections. No study of costs of antibiotic prophylaxis in elective cesarean section in a Swedish or Nordic context has been pursued. The aim of this study was to investigate if antibiotic prophylaxis is cost-reducing in elective cesarean section in Örebro County, Sweden. Methods All women undergoing elective cesarean in the Region Örebro County health care system during 2011–2012 were eligible for inclusion. Postoperative infections and risk factors for infections were registered. A hypothetical situation in which all participants had received antibiotic prophylaxis was compared to the actual situation, in which none of them had received antibiotic prophylaxis. The reduction in the risk of postoperative infections resulting from antibiotic prophylaxis was based on a meta-analysis. Costs for in-patient care of postoperative infections were extracted from the accounting system, and costs for out-patient care were calculated according to standard costs. Costs for antibiotic prophylaxis were calculated and compared with the cost reduction that would be implied by the introduction of such prophylaxis. Results The incidences of deep and superficial surgical site infection were 3.5% and 1.3% respectively. Introduction of antibiotic prophylaxis would reduce health care costs by 31 Euro per cesarean section performed (95% credible interval 4–58 Euro). The probability of cost-saving was 99%. Conclusions Antibiotic prophylaxis in elective cesarean section is cost-reducing in this health care setting. Our results indicate that the introduction of antibiotic prophylaxis in elective cesarean section can also be cost-saving in low infection rate settings. Trial registration Ethical approval was given by the Regional Ethical Review Board in Uppsala (registration number 2013/484).